2011
DOI: 10.1002/dev.20570
|View full text |Cite
|
Sign up to set email alerts
|

Alterations of sex‐typical microanatomy: Prenatal stress modifies the structure of medial preoptic area neurons in rats

Abstract: Prenatal stress disrupts normal sexual differentiation and behavior with concomitant alterations in brain development; however, its effects on the cytoarchitecture of neurons in the sexually dimorphic medial preoptic area (mPOA) of the hypothalamus is not known. Morphometric analysis of the mPOA of adult rats showed sex differences as neurons from control females had significantly greater numbers of basal dendritic branches and cumulative basal dendritic length as compared to control male neurons. Prenatal str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 73 publications
0
3
0
Order By: Relevance
“…High-level prenatal stress exerts profound impacts on the postnatal development of central nervous system in offspring and thus induces neurological deficits [2, 9, 20, 29]. Previous retrospective studies have shown that offspring from pregnant women exposed to natural and man-made unpleasant experience, such as earthquakes, wars or interpersonal relation disturbances, suffered from mental retardation, language hypoevolution, attention deficit, and neuropsychiatric impairment symptoms including schizophrenia, anxiousness and depression [17, 18, 3032, 34].…”
Section: Introductionmentioning
confidence: 99%
“…High-level prenatal stress exerts profound impacts on the postnatal development of central nervous system in offspring and thus induces neurological deficits [2, 9, 20, 29]. Previous retrospective studies have shown that offspring from pregnant women exposed to natural and man-made unpleasant experience, such as earthquakes, wars or interpersonal relation disturbances, suffered from mental retardation, language hypoevolution, attention deficit, and neuropsychiatric impairment symptoms including schizophrenia, anxiousness and depression [17, 18, 3032, 34].…”
Section: Introductionmentioning
confidence: 99%
“…At puberty, gonadal steroid hormones activate those prenatally organized structures to elicit sex-specific hormone-dependent behaviors. Factors that alter the prenatal steroid hormone environment can disrupt the structural organization and function of the offspring’s hypothalamic–pituitary–adrenal and gonadal axes (HPA and HPG, respectively) ( Glover et al, 2010 ; Gerecke et al, 2012 ; Jones et al, 2020 ). The consequence of this is altered behavioral expression that is dependent on the activation of those systems as shown in animal models ( Ng, 2000 ; Welberg and Seckl, 2001 ; Austin et al, 2005 ; Kapoor and Matthews, 2008 ; Xiong and Zhang, 2013 ; Jones et al, 2015 ; McGowan and Matthews, 2017 ; Matthews and McGowan, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Gestational stress alters the dendritic length and branching of neurons in the sexually dimorphic medial POA of adult males, suggesting possible modification of the neuronal activity and sexual behavior during adulthood (25). Exposure to the glucocorticoid receptor agonist, dexamethasone (DEX), during fetal stages reduce plasma testosterone levels, alter sexual maturation and reproductive behavior in male rat offpring (2628), as well as delay pubertal onset with irregular estrous cycle in female rodent offspring (29, 30).…”
Section: Introductionmentioning
confidence: 99%